URGENSI DIBENTUKNYA PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI BATAM - Halawa, Filemon (Ilmu Hukum Prima (IHP), 2023)
This research aims to determine the extent of the urgency of establishing an Industrial Relations Court (PHI) at the Batam District Court. Currently Batam City is still within the jurisdiction of the Industrial Relations Court at the Tanjungpinang District Court which is located on Jalan Raya Senggarang No.1 KM 14 Tanjungpinang City, Riau Islands Province. Suppose a rights dispute exists between workers, workers/labor organizations and employers, and an amicable agreement cannot be reached.  In that case, one of the parties who is not satisfied with the results of the Disnaker mediator's recommendations must take the route of a lawsuit through PHI at the Tanjungpinang District Court. In this research, the author raises four problems and limits the research problem. Among other things, first, what is the legal reason for the urgency of establishing an Industrial Relations Court at the Batam District Court? Second, what are the obstacles that, until now, PHI at the Batam District Court has not been formed? thirdly, what is the solution so that PHI at the Batam District Court is formed to provide a sense of justice for justice seekers in industrial relations disputes? fourth, what obstacles areexperienced by workers, laborers, or labor organizations that make it difficult to file an industrial relations dispute lawsuit if there is no peace agreement with the employer? The author uses the legal theory of development put forward by Mochtar. Kusumaatmadja is an analytical tool to find answers to four research questions. Of four research questions with normative-empirical research methods. It was found that the final result was that there was a great urgency for the Industrial Relations Court in Batam to be able to realize the principles of simple, fast and low-cost justice for people seeking justice in Batam.